SEEKING THE IDEAL SUPERVISORY INVOLVEMENT IN PROJECT-BASED LEARNING - AlJassmi, Hamad (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Finding the right balance of mentorship and students’ independence, as students progress throughout different stages of their project-based learning, is key to the success of this pedagogical approach. Students and advisors must have a shared understanding of their roles and responsibilities, as well as the extent of independence anticipated from students. This presentation summarizes literature and research outcomes of what are deemed as the ideal: (1) student group composition, (2) level of involvement and mentorship of the course instructor, and (3) level of learning independence expected from students across different project stages. Insights from this presentation serve as basis for guiding faculty members aiming to yield the most out of their project-based teaching methods.